Water-use accounts in CPWF basins: Simple water-use accounting of the Mekong Basin - Kirby, M.; Mainuddin, M.; Eastham, Judy (CGIAR Challenge Program on Water and Food, 2010)
This paper applies the principles of water-use accounts, developed in the first of the series, to the Mekong River basin in Southeast Asia. The Mekong Basin covers six countries, the River rises in China, but there are substantial downstream tributaries from Thailand, Laos, Cambodia, and Vietnam, and from a small area in Myanmar. A unique feature is the reverse flow from the Mekong to the Tonle Sap via the Tonle Sap River at the height of the wet season flow and its ebb as the river levels fall. Net runoff is about 37% of total precipitation. Forest and woodland cover 43% of the basin and use about 33% of the precipitation. Grassland covers much of the upper part of the Basin, consuming about 6% of the precipitation. Irrigated agriculture covers just 6% of the Basin and uses about 6% of the water (excluding runoff). Climate change, using an assumed change in rainfall distribution, shows that with the expected shorter and more intense rainy season, and longer and more intense dry season, both floods and seasonal water shortages may be exacerbated. Keywords: Water use accounts, Mekong basin, top-down modeling, basin water use